Additive Lie derivations on the algebras of locally measurable operators - Juraev, Ilhom; Gaber, Jaafar (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Let M be a von Neumann algebra without central summands of type I . We are studying conditions that an additive map L on the algebra of locally measurable operators has the standard form, that is equal to the sum of an additive derivation and an additive center-valued trace.